The Role of Religiosity and Patriotism in Improving Taxpayer Compliance - Ietje Nazaruddin (Universitas Muhammadiyah Yogyakarta, Indonesia, 2019)
The purpose of this study is to examine the direct effect of religiosity on taxpayer compliance. In addition, this study also examines the indirect effect of religiosity on taxpayer compliance using the mediation variables of taxpayer patriotism. The data were gathered survey method that was able to collect as much 78 data that can be used for analysis. The validity, reliability of instruments and classical assumptions test were conducted before testing the hypothesis. Simple and multiple regression were used to test the relationship between variables. The indirect influence was tested using Hayes's bootstrapping method. The results showed that the level of religiosity had a positive effect on patriotism and taxpayer compliance. High patriotism would increase taxpayer compliance. The results also provided empirical evidence that there was an indirect influence of religiosity on taxpayer compliance through the mediation of patriotism.